Penanaman Akhlak di MI Miftakhul Akhlaqiyah Melalui Metode Teladan: Membangun Karakter Dengan Keteladanan Guru - Ahmad Zainal Abidin (Hawari: Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
The implementation of the exemplary teaching method in Madrasah Ibtidaiyah Miftakhul Akhlaqiyah, Semarang, represents an efficacious strategy for the inculcation of moral values in students, particularly in light of the challenges posed by globalisation and the rapid dissemination of modern information, which frequently exert an adverse influence on student character. The findings of this study, based on 12 days of participatory observation, indicate that teachers who consistently model discipline, manners, and mutual respect are effective in fostering positive character in students. The development of discipline, manners in communication, and respect among students is contingent upon the examples set by teachers in their daily lives. Teachers not only disseminate moral values in theory, but also demonstrate their practical application in daily life, thereby facilitating students' internalisation of positive attitudes. The recommendations derived from this study underscore the pivotal role of teachers as exemplars in character education, underscoring their significant influence in shaping students' personalities through tangible examples within the school environment.